Risk Management and Sharia Compliance in Crypto Staking: A Systematic Literature Review - Maulana Asykari Muhammad; Fitroh Fitroh; Rinda Hesti Kusumaningtyas (Politeknik Negeri Batam, 2026)
The adoption of Decentralized Finance (DeFi) introduces multidimensional risks that challenge institutional stability and Sharia jurisprudential standards. Existing studies often isolate technical security measures from theological compliance, creating a gap in governing digital assets under Sharia principles. This study aims to systematically review the intersection of technical risk mitigation and Sharia compliance in crypto-asset mechanisms. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines, analyzing 32 peer-reviewed articles published between 2023 and 2025. The synthesis reveals that technological and operational vulnerabilities in smart contracts induce elements of Gharar or uncertainty and Maysir or speculation, which conflict with the Maqasid al-Shariah objective of Hifzul Mal or protection of wealth. To bridge the gap between cryptographic protocols and Fiqh Muamalah or Islamic commercial law, this review identifies Enterprise Architecture (EA), specifically the TOGAF Architecture Development Method (ADM), as a structural integration framework. EA functions as a governance framework that systematically maps Sharia constraints directly into executable IT control layers. Specifically, the Business Architecture layer enforces contract validity, the Information Systems Architecture layer standardizes auditable data flows, and the Technology Architecture layer secures the consensus mechanics. The findings conclude that future research must transition from conceptual reviews to empirical implementations, particularly by designing Sharia-compliant enterprise architectures for post-Merge Ethereum staking protocols.